Detection and control of Ganoderma boninense : strategies and perspectives - Hushiarian, Roozbeh; Yusof, Nor Azah; Dutse, Sabo Wada (SpringerOpen, 2013)
The oil palm, an economically important tree, has been one of the world’s major sources of edible oil and a significant precursor of biodiesel fuel. Unfortunately, it now faces the threat of a devastating disease. Many researchers have identified Ganoderma boninense as the major pathogen that affects the oil palm tree and eventually kills it. But identification of the pathogen is just the first step. No single method has yet been able to halt the continuing spread of the disease. This paper discusses the modes of infection and transmission of Ganoderma boninense and suggests techniques for its early detection. Additionally, the paper proposes some possible ways of controlling the disease. Such measures, if implemented, could contribute significantly to the sustainability of the palm oil industry in South East Asia.